A Cross-Sectional Analysis of the Effect of Obesity on Sperm Quality in Infertile Couples - Rahila Imtiaz, Sarah Riaz, Melissa Mazcuri, Poonam Kumari, Ulvina, Asma Lqbal, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The obesity pandemic is emerging which is clearly because of changes in caloric habits and lifestyles of people worldwide. A number of serious medical problems are associated with obesity. One of them is infertility. Objective: The main purpose of this research was to evaluate the relationship of body mass index (BMI) with standard semen parameters by measuring hip circumference and waist circumference. Study design: A cross-sectional study Place and Duration: This study was conducted at Abassi Shaheed Hospital Karachi hospital from November 2021 to November 2022. Methodology: All infertile couple who visited gynaecology outpatient department for infertility treatment interviewed and after taking relevant history of both partners total of 180 men were enrolled in this research . By using the standard methods, the weight and height of the patients was measured. Moreover, their WC (waist circumference) and hip circumference were also measured. After two to five days of abstinence from coitus, the patients were advised to give the semen in laboratory for semen analysis. First, the liquefaction was done. Later, the Makler counting chamber was used to analyze the semen. A number of semen parameters were noted by using the Worth Health Organization criteria Results: Most of the individuals were from the age group of 31 to 40 years. Most of the men (n=144) were having primary infertility, representing 80% of the total sample size. The waist-hip ratio was seen in the majority of the men. There was a negative link seen between semen parameters and WHR. The majority of the men were having a body mass index of 23 to 27 kg/m2, representing 51.5% of the total sample size. A total of 27 males were having mildly decrease sperm concentration, representing 15% of the sample size. On the other hand, a total of 35 men with mildly decrease sperm counts, represented 19.4 percent of the sample size. Conclusion: There is a negative relationship between semen parameters (total sperm count, total motility, sperm concentration, and total progressive motility) and WHR. Keywords: Semen analysis, obesity, waist-hip ratio, infertility